Determinants of Commitment and Performance of Teachers in the National Training Program in Kunming, Yunnan - Wang, Wenwen (Scholar: Human Sciences, 2024)
Purpose: This paper aims to examine the determinants of commitment and performance of teachers in the National Training Program in Kunming, China. The conceptual framework proposed a causal relationship between leadership, emotion, commitment, knowledge, climate, and performance. Research design, data, and methodology: The researcher adopted a quantitative technique (n=500) to collect the data by questionnaire distribution. Non-probability sampling included judgmental sampling to select four Kunming primary and secondary schools, quota sampling to define the sample size, and convenience sampling to collect data and distribute the questionnaires online and offline. The researcher used structural equation modeling (SEM) and confirmatory factor analysis (CFA) to conduct the data analysis, including model fit, reliability, and construct validity. Results: The results showed that leadership and emotion significantly affected commitment and used commitment as an intermediate variable to influence teacher performance. Knowledge and climate also had a significant effect on teacher performance. Climate strongly affected teacher performance, followed by commitment and knowledge. Conclusions: This indicated that this study achieved the research objectives. Therefore, we suggested that to make the National Training Program (NTP) more effective, policymakers and programmed operators could increase their investment in the factors that affected teacher performance in the NTP and optimize the proportion of investment.